Choice of three different intramedullary nails in the treatment of trochanteric fractures: Outcome, analysis and consideration in midterm. (October 2019) - Persiani, Pietro; Ranaldi, Filippo Maria; Gurzì, Michele; Formica, Alessandro; Graci, Jole; De Cristo, Claudia; Grasso, Raffaele; Villani, Ciro
Highlights: Synthesis of lateral femoral neck fractures with intramedullary nail has a biomechanical superiority instead of other kind of synthesis, respects soft tissues and decreases operative time. In literature, no one study demonstrated a real superiority of a type of nail over another one, in relation to the patients functional outcomes. Analysing the 3 different nails, all provided a stable synthesis, clinical and radiological bone healing, with no statistically significant differences highlighted. The surgical knowledge of the individual surgeon is the only determining factor for the success in lateral femoral neck fractures treatment. Abstract: The purpose of this study is to compare the results obtained using three different systems of osteosynthesis, developed for the surgical treatment of fractures of the trochanteric region of the femur, based on the principle intramedullary nailing: the Gamma nail, the Affixus nail and the ZNN nail. This is a retrospective study: 72 trochanteric fractures treated with the Gamma nail, 68 treated with the Affixus nail and 69 treated with the ZNN nail, between the years 2012 and 2014, with the prerequisite of a minimum follow-up of 18 months. The fractures were classified according to the AO system; the most commonly reported subtype was the A2 fracture. Clinical and radiographic examinations were performed, both at hospital admission and post-operatively, at 1, 3, 6, 12 and 18 months. Of the 209 patients, 171 were women and 38 were men. The average age was 83.12 years old. All three systems guaranteed an early mobilization and ambulation in most of the patients. There were no significant differences in the use of the three nails in terms of recovery of previous functional capacity, or in terms of the time required for the fracture to heal. There were no advantages encountered with the use of one intramedullary nail over another and, in particular, when observing the complications and patient outcome, there were no statistically significant differences detected.